2009
DOI: 10.1021/ol9022563
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrically 4,7-Disubstituted Benzothiadiazoles as Efficient Non-doped Solution-Processable Green Fluorescent Emitters

Abstract: Asymmetrically 4,7-disubstituted benzothiadiazole derivatives involving a carbazolyl moiety at one end and a solubilizing dendron at the opposite end have been synthesized and characterized. A two-layer electroluminescent device based on one of these solution-processed molecular emitters revealed a maximal luminous efficiency of approximately 10.6 cd A(-1) and green light emission with CIE coordinates (0.34, 0.58).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…Triazine, oxadiazole, triazole, cyno-substituted benzene and benzothiadiazole are usually used as acceptor units, while carbazole, arylamine, phenothiazine and their derivatives are commonly adopted as the donor moieties for bipolar structures for OLEDs [ 15 , 16 , 17 , 20 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Herein, we utilize phenothiazine and 9,9-diphenyl-9,10-dihydroacridine as the donor unit, while oxadiazole derivatives 2,5-bis(4-bromophenyl)-1,3,4-oxadiazole and 2-(4-bromophenyl)-5-phenyl-1,3,4-oxadiazole are employed as the acceptors to synthesize four distorted A-D and D-A-D type fluorescent materials, 2,5-bis(4-(10H-phenothiazin-10-yl)-1,3,4-oxadiazole (2PTZ-OXD), 2-(4-(10H-phenothiazin-10-yl)-1,3,4-oxadizaole (PTZ-OXD), 2,5-bis(4-(9,9-diphenyl-9,10-dihydroacridine)phenyl)-1,3,4-oxadizaole (2DPAc-OXD) and 2-(4-(9,9-diphenyl-9,10-dihydroacridine)phenyl)-1,3,4-oxadiazole (DPAc-OXD).…”
Section: Introductionmentioning
confidence: 99%
“…Triazine, oxadiazole, triazole, cyno-substituted benzene and benzothiadiazole are usually used as acceptor units, while carbazole, arylamine, phenothiazine and their derivatives are commonly adopted as the donor moieties for bipolar structures for OLEDs [ 15 , 16 , 17 , 20 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Herein, we utilize phenothiazine and 9,9-diphenyl-9,10-dihydroacridine as the donor unit, while oxadiazole derivatives 2,5-bis(4-bromophenyl)-1,3,4-oxadiazole and 2-(4-bromophenyl)-5-phenyl-1,3,4-oxadiazole are employed as the acceptors to synthesize four distorted A-D and D-A-D type fluorescent materials, 2,5-bis(4-(10H-phenothiazin-10-yl)-1,3,4-oxadiazole (2PTZ-OXD), 2-(4-(10H-phenothiazin-10-yl)-1,3,4-oxadizaole (PTZ-OXD), 2,5-bis(4-(9,9-diphenyl-9,10-dihydroacridine)phenyl)-1,3,4-oxadizaole (2DPAc-OXD) and 2-(4-(9,9-diphenyl-9,10-dihydroacridine)phenyl)-1,3,4-oxadiazole (DPAc-OXD).…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown, however, the importance of symmetry break in many fields of light technology . In this context, BTD derivatives had their C 2 ‐symmetry broken and were successfully applied as dyes with enhanced two‐photon absorption cross sections, dye‐sensitized solar cells, redox‐tunable donor‐acceptor systems, metal sensors,, and for solution‐processed molecular emitters with green light emission . Despite the fact that some outstanding works have already been published describing the synthesis of non‐symmetric BTD derivatives, there are still much to be achieved, and several drawbacks need to be overcome in order to develop novel applications for BTDs.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al introduced non-planar binaphthyl groups and obtained a red device with a luminescence efficiency (LE) of 1.95 cd A À1 and a high maximum luminance of 8315 cd m À2 at a low turn-on voltage of 2.2 V. [5] Li et al synthesized a asymmetrically 4,7disubstituted benzothiadiazole derivative in which 3,5-di(psec-butoxylphenyl)phenyl groups were utilized to gain better films, and a green device based on that revealed a LE of 10.6 cd A À1 with CIE coordinates (0.344, 0.580). [6] Wang et al reported a color-stable blue OLED with a LE of 5.3 cd A À1 , a maximum external quantum efficiency (EQE) of 4.5 %, and CIE coordinates of (0.155, 0.086). [7] In spite of the rapid development, small-molecule SP-OLEDs exhibiting excellent performance with a single-layer device have been rarely reported so far, especially for highly efficient blue SP-OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al. synthesized a asymmetrically 4,7‐disubstituted benzothiadiazole derivative in which 3,5‐di( p ‐ sec ‐butoxylphenyl)phenyl groups were utilized to gain better films, and a green device based on that revealed a LE of 10.6 cd A −1 with CIE coordinates (0.344, 0.580) 6. Wang et al.…”
Section: Introductionmentioning
confidence: 99%